Dialectal grammatical differences in oral narratives of school-aged Indigenous Australian children - Pearce, W.; Williams, Cori; Steed, W. (2015)
Purpose: Children's oral language samples are regularly analysed in order to describe levels of language development and develop learning goals. However, diagnostic interpretation of language samples from Indigenous Australian children is problematic due to overlap between features of Aboriginal English and features of language impairment in the mainstream non-Indigenous population. Limited studies explore the use of Aboriginal English and its diagnostic impact. This research, therefore, describes the grammatical features of language samples from one group of Indigenous Australian children. Method: Participants were 19 children aged 8;1–13;4 from the same school in a regional city with 100% Indigenous enrolment. The Test of Narrative Language was administered, eliciting three oral narratives, and features of Aboriginal English grammar were coded. Result: Dialect density was highly variable and greater in the Verb Phrase than in the Noun Phrase or Clause Structure. High teacher ratings of oral language ability aligned with lower measures of dialect density and higher grammatical accuracy for Standard Australian English. Grammatical accuracy was frequently higher for Aboriginal English than Standard Australian English. Conclusion: Over-identification of language impairment was identified as a risk when evaluating the language ability of Indigenous Australian children.